1997
DOI: 10.1143/jjap.36.1589
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of W-Si-N Film Microstructure with Barrier Performance against Cu Diffusion

Abstract: A microsphere/cylinder waveguide resonator for directly coupling a light beam into a waveguide is proposed. To avoid unwanted resonance in the core, a metallic core is used on which a high refractive index waveguide is placed to form a shell structure. The input or output light coupling is realized by using the leaky mode of a specially designed curved waveguide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It was reported that the amorphous structure of reactive-sputter-deposited WSiN layers can be preserved even after annealing at 850ЊC. 33 It was also reported that a very thin (4 nm) WSiN layer can be formed on the WSi x surface by ECR N 2 plasma nitridation and that it functioned as an excellent barrier to dopant diffusion. 34 In this work, the very thin and thermally very stable WSiN layers gave a great help to suppress the Cu diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the amorphous structure of reactive-sputter-deposited WSiN layers can be preserved even after annealing at 850ЊC. 33 It was also reported that a very thin (4 nm) WSiN layer can be formed on the WSi x surface by ECR N 2 plasma nitridation and that it functioned as an excellent barrier to dopant diffusion. 34 In this work, the very thin and thermally very stable WSiN layers gave a great help to suppress the Cu diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…In the equilibrium structure of W 2 N, all the N atoms are accommodated in half of the available octahedral interstitial sites. 18,25,29 It was reported that nitrogen in the W 2 N film started to evaporate to vacuum at about 820°C, and was fully released after annealing at 900°C. The thermal annealing above 800°C has removed part of the excessive interstitial N atoms, and consequently the W 2 N ͑111͒ interplanar distance shifts closer to the standard value.…”
Section: Discussionmentioning
confidence: 99%
“…Ternary amorphous metallic thin films such as Ti–Si–N [ 1 , 2 , 3 , 4 ], Mo–Si–N [ 5 , 6 ], Zr–Si–N [ 7 , 8 , 9 , 10 ], Ta–Si–N [ 11 , 12 , 13 , 14 , 15 , 16 ], and W–Si–N [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ] have received considerable attention for high temperature diffusion barrier applications. These materials have shown to be chemically inert against reactions with gold [ 4 , 11 , 24 ], silver [ 11 ], copper [ 12 , 13 , 14 , 16 , 17 , 20 ], aluminum [ 18 , 25 ], and platinum [ 26 , 27 , 28 ] metallization at elevated temperatures, thereby providing the low diffusivities required for a diffusion barrier. Moreover, their amorphous structure sustains even at temperatures above 800 °C [ 15 , 20 , 21 ], preventing the formation of grain boundaries which act as rapid diffusion paths.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have shown to be chemically inert against reactions with gold [ 4 , 11 , 24 ], silver [ 11 ], copper [ 12 , 13 , 14 , 16 , 17 , 20 ], aluminum [ 18 , 25 ], and platinum [ 26 , 27 , 28 ] metallization at elevated temperatures, thereby providing the low diffusivities required for a diffusion barrier. Moreover, their amorphous structure sustains even at temperatures above 800 °C [ 15 , 20 , 21 ], preventing the formation of grain boundaries which act as rapid diffusion paths.…”
Section: Introductionmentioning
confidence: 99%